High Strangeness: Deluxe Edition. - DABBENE, PETER (Foreword Reviews)
The article reviews *High Strangeness: Deluxe Edition*, a graphic anthology by Daniel Noah that weaves disparate paranormal incidents—such as UFO sightings, Bigfoot encounters, and dream simulations—into a time-spanning narrative. Each of the five chapters features distinct artistic styles that enhance the eerie and otherworldly atmosphere, while subtle connections between stories create a cohesive experience. The anthology also includes essays that provide background on paranormal themes like men in black and astral travel. This collection offers a broad exploration of paranormal phenomena through both storytelling and supplementary nonfiction content.